2014
DOI: 10.4238/2014.january.3.1
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic analysis of endothelial progenitor cells exposed to folic acid in type 1 diabetes mellitus

Abstract: ABSTRACT. We investigated the effects of type 1 diabetes mellitus (T1DM) on endothelial progenitor cells (EPCs) at the molecular level and assessed the therapeutic potential of folic acid (FA) in DM. We downloaded the gene expression profile of the EPCs from T1DM patients before and after treatment with FA and from healthy controls. We identified the differentially expressed genes (DEGs) in the EPCs from T1DM patients before and after a four-week period of FA treatment and compared them with those obtained fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…92 Moreover, folic acid treatment also shows to normalize the majority of the altered gene expression profiles of EPCs from patients with type 1 DM compared with healthy subjects. 93 In the diabetic mouse model, the overexpression of eNOS in EPCs improves their proangiogenic and antiatherogenic properties. 94 Interestingly, recent studies have suggested that hydrogen sulfide has proangiogenic effects, which improve wound healing via the restoration of EPC functions in diabetic mice.…”
Section: Biological Therapiesmentioning
confidence: 99%
“…92 Moreover, folic acid treatment also shows to normalize the majority of the altered gene expression profiles of EPCs from patients with type 1 DM compared with healthy subjects. 93 In the diabetic mouse model, the overexpression of eNOS in EPCs improves their proangiogenic and antiatherogenic properties. 94 Interestingly, recent studies have suggested that hydrogen sulfide has proangiogenic effects, which improve wound healing via the restoration of EPC functions in diabetic mice.…”
Section: Biological Therapiesmentioning
confidence: 99%
“…Fang assessed the effect of FA treatment on T1DM by analyzing the gene expression profile of EPCs (Endothelial progenitor cells) from T1DM patients treated with FA and comparing it to that from healthy controls, and showed that FA normalized a majority of changes in gene expression induced by T1DM (99.6%), suggesting the therapeutic potential of FA in the treatment of T1DM [4]. Magnesium is an essential ion involved in glucose homeostasis [12].…”
Section: Effects Of Folic Acid and Magnesium Co-administration On Blood Glucose Levels Inmentioning
confidence: 99%
“…Major contributory factors are hyperglycemia, hypertension, dyslipidemia, overweight, and tobacco use which are amenable to prevention and treatment [2]. The free radical scavenging properties and possible antioxidant activity of folic acid are reported [3,4], assessed the effect of FA treatment on T1DM by analyzing the gene expression profile of EPCs (Endothelial progenitor cells) from T1DM patients treated with FA and comparing it to that from healthy controls, and showed that FA normalized a majority of changes in gene expression induced by T1DM (99.6%), suggesting the therapeutic potential of FA in the treatment of T1DM.…”
Section: Introduction mentioning
confidence: 99%